1992
DOI: 10.1152/jappl.1992.73.4.1457
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of hyaluronan in the rabbit pleural space

Abstract: Hyaluronan influences lung fluid balance. The clearance of lung hyaluronan by way of the pulmonary lymphatics and the pleural space is increased when fluid flux into the interstitium is increased. The purpose of this study was to determine the rate at which hyaluronan is removed from the pleural space. We injected hyaluronan, labeled with tritium in the acetyl group, into the pleural space of six rabbits. The appearance of [3H]H2O in serum was measured over time to calculate the turnover rate of hyaluronan. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Pleural glucose and lactic dehydrogenase concentrations are similar, or slightly smaller than in serum (Sahn & Light 1989); in inflammation, their increase provides, together with a low pH, the most important clinical indicator to distinguish between transudative or exudative pleural disease (Sahn & Light 1989, Joseph et al 2001. Normal pleural fluid HA content is~0.7 lg mL À1 (Allen et al 1992); however, it dramatically increases in malignant pleural effusion (Thylen et al 2001), providing a significant prognostic value for malignant mesothelioma.…”
Section: Pleural Fluid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleural glucose and lactic dehydrogenase concentrations are similar, or slightly smaller than in serum (Sahn & Light 1989); in inflammation, their increase provides, together with a low pH, the most important clinical indicator to distinguish between transudative or exudative pleural disease (Sahn & Light 1989, Joseph et al 2001. Normal pleural fluid HA content is~0.7 lg mL À1 (Allen et al 1992); however, it dramatically increases in malignant pleural effusion (Thylen et al 2001), providing a significant prognostic value for malignant mesothelioma.…”
Section: Pleural Fluid Compositionmentioning
confidence: 99%
“…Normal pleural fluid HA content is ~0.7 μg mL −1 (Allen et al . ); however, it dramatically increases in malignant pleural effusion (Thylen et al . ), providing a significant prognostic value for malignant mesothelioma.…”
Section: Pleural Fluid Origin Volume and Compositionmentioning
confidence: 99%
“…Based on the minute quantities of pleural liquid hyaluronan detected in normal control rabbits, Allen et al [5] concluded that the pleural liquid hyaluronan would have a negligible effect on pleural liquid viscosity and thus would not function as an effective hydrodynamic lubricant (whose properties depend on pleural liquid viscous forces). Moreover, the increase in hyaluronan concentration caused by the increased ventilation in rabbits breathing 3% CO 2 is likely to cause only a slight increase in pleural liquid viscosity.…”
Section: Factors Affecting Pleural Liquid Hyaluronan Concentrationmentioning
confidence: 99%
“…The liver specifically eliminates endogenous HA, therefore rapid and continuous elimination of HA from the circulation by the liver was expected. 13,15,19 The kidneys had lower levels than the liver but more than the heart, spleen, and bladder, suggesting that urinary excretion may be another potential route for eliminating the small amounts of HA absorbed systemically from the lung. 1214 HA content in the bladder tissue was low at all time points.…”
Section: Discussionmentioning
confidence: 99%
“…7–13 Thus, HA serves as an interesting polymer to carry drugs. Absorption of HA after subcutaneous, 1418 intraperitoneal, 19 oral, 20,21 and intravenous injection 2224 has been reported, but the fate of HA after pulmonary administration is not well understood. Recent work suggesting that HA may be useful for inhaled drug delivery motivates a better understanding of HA fate after pulmonary administration.…”
Section: Introductionmentioning
confidence: 99%